THE RELATIONSHIP BETWEEN CORPORATE SOCIAL RESPONSIBILITY AND MARKET SHARE: EVIDENCE FROM NIGERIA IN WEST AFRICA - Adekanmi, Aderemi Daniel; Ololade, Babatunde Moses; Adeoye, Ebunoluwa Tokunbo (Annals of Spiru Haret University. Economic Series, 2022)
The study examined the effect of corporate social responsibility on market share of listed manufacturing firm in Nigeria. It specifically examined the effect of internal environmental cost on market share of listed manufacturing firms in Nigeria, it also examined the effect of external environmental cost on market share of listed manufacturing firms in Nigeria. The study predicated of stakeholder’s theory. The study adopted Ex post facto research design and secondary data was gathered to analyse the relationship between the variables. The population of the study consisted of forty-two manufacturing listed in the Nigeria Stock Exchange, while ten samples were collected from the population. The data collected were analysed through descriptive statistic, Error Correction MODEL (Long and short run relationship), and correlation matrix regression analysis. The result of the findings revealed that internal environmental cost has positive and significant effect on market share of listed manufacturing firms in Nigeria (p= 0.1.454 > 0.05) and external environmental cost has positive and significant effect on market share of listed manufacturing firms in Nigeria(p=0.6757 > 0.05) The study concluded that CSR activities such as internal environmental cost and external environmental cost through donations to the society where they operate their business and other social and infrastructural facilities reflect in their annual financial statement as external cost incurred during the year. The study recommended that Nigerian manufacturing firms take advantage of external environmental costs by investing more on the business's environment, notably via corporate social responsibility Key: Corporate Social Responsibility, Internal Environmental Cost, External Environmental Cost, Market Share